Correlative coding with clipping and filtering technique in OFDM Systems - Yusof, S. K.; Fisal, Norsheila (2003)
The major setbacks of Orthogonal Frequency Multiplexing (OFDM) is its peak-to-average power ratio (PAPR) and intercarrier interference (ICI). The occurrence of these factors restricts its application. Here, the clipping and filtering PAPR reduction technique is king investigated to reduce the PAPR and out-of-band radiation simultaneously by implementing correlative coding. This paper focuses on the preliminaty measurement studies that was canid out. It is shown thmugh simulation that the collaboration of these techniques gives a reasonable PAPR reduction and improves the out-of-band radiation.